STUDY OF DEVELOPMENT STRATEGY OF SELF-OWNED BRAND PASSENGER VEHICLE OF DONGFENG UNDER THE NEW ENERGY VEHICLE ERA - He, Wu; Bi, Chuanchen (International Journal of Engineering Technologies and Management Research, 2022)
With the continuous development of China, energy security and environmental protection gradually become national strategic issues, and the automotive industry as the national economic development foundation and pillar industry is affected by such two national strategic issues. To get rid of the dependence on imported petroleum and achieve energy conservation and emission reduction, it is inevitable for China to strive to develop new energy vehicle. In recent ten years, the new energy vehicle industry has developed rapidly with the policy support of the government of China. The Dongfeng Motor Group as traditional automobile factory, under the tide of new energy vehicle, bears the double attack from the new power of vehicle manufacturing and traditional automobile factory, and confronts the double pressure of product transformation and improvement of self-owned brand's market share. The self-owned brand passenger vehicle of Dongfeng is researched in the PESTE analysis, FIVE FORCES analysis and SWOT analysis, and some new suggestions concerning product strategies and market strategies are offered through interview survey, so that Dongfeng Motor Corporation Passenger Vehicle Company can grasp the development opportunity to twist the adverse situation in new situation and can provide certain consideration and reference for the future development of other motor corporations.